Molecular mechanisms underlying the motivational effects of nicotine - Brunzell, Darlene H. (2009)
In addition to the primary rewarding properties of nicotine and the alleviation of withdrawal symptoms, cues associated with smoking are critical contributors to maintenance of smoking behavior. Nicotine-paired cues are also critical for precipitating relapse after smoking cessation. An accumulation of evidence suggests that repeated exposure to tobacco, including the primary psychoactive ingredient, nicotine, changes brain neurochemistry in a way that promotes the control that cues associated with smoking or other rewards have over behavior. This chapter will consider the neurochemical mechanisms underlying these neuroadaptations. Targeting these molecular alterations may provide novel treatments for smoking cessation.